Analisis Kebijakan Kriminal terhadap Kejahatan Dalam Rumah Tangga - JP Widodo (Law Faculty of Universitas Bandar Lampung, 2006)
The violarce crime in domestic family is crime, that cause dilemma in law enforcement, that is the filosofi to maintenance familyâs harmony, but tend to permissive crime, hor ever trictly to process to suspec will broke lement of familyâs harmony.Appearing of act number 23 , 2003 is fellortÂ toÂ safe victim of violances crime in domestic family, but teminology ofâviolancei n the act not specific , so can cause unfair inÂ law interpretationt forÂ victim violance domestic family.